The use of intraoperative mannitol during the laparoscopic nephrectomy in living kidney donor and the prevention of delayed graft function - Fernando Giron-Luque; Nasly Patino-Jaramillo; Yenny Baez-Suarez; Andrea García-López (Urología Colombiana)
Background and objectives: The administration of mannitol during laparoscopic hand-assisted nephrectomy in the living donor has been controversial with various recommendations about it. This study aims to evaluate the effect of the intraoperative mannitol in the living kidney donor and the incidence of delayed graft function (DGF). Methods: This study was a retrospective observational study with living kidney transplant recipients and donors who underwent laparoscopic hand-assisted nephrectomy at Colombiana de Trasplantes from January 2015 to September 2019. We assessed the impact of mannitol administration in living donors on the main transplant outcomes such as DGF, urinary volume, acute rejection, and mortality at 3 months of follow-up. We performed a descriptive analysis of demographics and clinical variables in our cohort. Results: A total of 367 recipients were evaluated. The incidence of DGF was 5.9% without mannitol versus 6.2% with mannitol (p = 0.99). The acute rejection episodes (12.2% without mannitol versus 4.7% with mannitol) had a trend difference between the comparative groups, but it was still not significant in the bivariate analysis (p = 0.06). The mortality rate in the recipient was not significant (p = 0.69). The mean serum creatinine did not have significant differences at 1 and 3 months of follow-up comparing both groups. Conclusion: The use of mannitol in living donors does not have a significant impact on the incidence of DGF in kidney recipients. A trend of association between mannitol administration and reduced acute rejection episodes was observed, though it was not statistically significant.